Perfil de mães adolescentes de São José do Rio Preto e cuidados na assistência pré-natal - Faria, Denise Gonzales Stellutti de (2007)
The growing index of pregnancy in adolescence represents a social and public health issue for Brazil as well as for other countries, due to the organic, psychological and social consequences that pregnancy accounts for this age group. Studies have been showing that the pregnant adolescents begin prenatal care later, and they receive them in a smaller number when compared to the twenty year-old women or over. The quality of the prenatal influences directly on the results of the pregnancy among adolescents. This study aims to: identify the sociodemographic profile and cares in the prenatal care of adolescent mothers assisted by SUS; know the characteristics of the sexual and reproductive life, identify the characteristics of the prenatal and childbirth type, describe the type of orientations received in the prenatal care and evaluate the perinatal outcome according to low weight, prematurity and Apgar. In this descriptive study, 84 adolescent mothers with childbirth between 01/10/2004 to 01/12/2004 were interviewed. The results were: 96.4% in the age group between 15 to 19 years; 73.8% lived with a partner; 65% received up to three minimum wages; 79.3% had never worked; 52.4% were enrolled at a school when they became pregnant. The mean age of the first sexual relationship was 15 years; 64.3% reported the use of contraceptive method; only 9.5% used it when they became pregnant; 100% of the adolescents received prenatal care; 58.5% began in the first quarter of pregnancy; 84.6% had six to twelve consultations; 83.3% were primiparas and 83.3% had not planned their pregnancy. The following complications were observed during pregnancy in the mothers: 44% anemia; 35.7% urinary infection; 14.3% vaginal bleeding;14.2% high blood pressure; 2.4% gestational diabetes and 1.2% eclampsia. Caesarian childbirth was performed in 61.9%. Regarding the orientation type received in the prenatal care; 85.7% of the adolescents received orientation for not taking use of medication without medical prescription; 73.8% for not using drugs; 72.6% the damages of smoking and alcoholic drink; 70.2% in relation to the feeding type in the gestation; 54.8% on the cares with the teeth; 72.6% on the signs of the labor beginning; 60.7% the childbirth types; 76.2% on the importance of the maternal breastfeeding; 17.9% the baby's bath and 18.3% on the umbilical cord. According to the newborns: 6% had low weight; 6% were premature; Apgar was superior to 8 in 86.9% of the cases in the first minute, and 95.1% in the fifth minute. In this group of adolescents, appropriate prenatal care (the beginning in the first quarter and minimum number of six consultations) allowed good results, in spite of the mothers' age to be associated with risk pregnancies. The percentage of complications in the newborns was low.